KORELASI MAP (MEAN ARTERIAL PRESSURE) DAN PROTEIN URINE SEBAGAI SKRINING KONDISI PREEKLAMPSIA PADA IBU HAMIL - Mandani, Chesya Putri; Sugijati, Sugijati; Wiyati, Ari Kusmi (Malang Journal of Midwifery (MAJORY), 2024)
Preeclampsia is a complication characterized by an increase in maternal blood pressure and maternal urine protein. The condition of preeclampsia has negative impacts on the mother and fetus, such as death. To prevent this condition from occurring, screening can be carried out as early as possible with the aim of early detection and treatment to reduce maternal mortality and cases of preeclampsia. The aim of this study was to determine the relationship between MAP examination and urine protein examination as a preeclampsia screening at the Mulyorejo health center, Malang city. Analytical correlation research design with a Cross Sectional approach, with a population of 78 respondents, sampling using Purposive Sampling Technique with a sample size of 65 respondents from pregnant women aged ? 20 weeks who met the inclusion criteria. The research instruments used a sphygmomanometer and urine dipstick. This study used the bivariate Spearman Rank Correlation test (? = 0.05). The research results showed that MAP in pregnant women was mostly negative at 63.1% and urine protein was almost entirely negative at 95.4%. The results of the Spearman Rank Correlation test showed a p-value of 0.020 < 0.05, which means there is a relationship between MAP and urine protein as a preeclampsia screening. MAP and urine protein are one of the screening methods for pre-eclampsia in pregnant women. So, it is hoped that pregnant women will routinely carry out pregnancy checks as an early detection of pregnancy complications, especially preeclampsia.